Faktor-Faktor yang Mempengaruhi Pemberian ASI Eksklusif pada Ibu Bekerja - Ulya, Ni'matul; Prajayanti, Hilda (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2024)
Exclusive breastfeeding is a very important part of fulfilling baby's nutrition to achieve optimal. Exclusive breastfeeding for every baby can prevent infections and diarrhea in children and save costs for poor families. It is proven that exclusive breastfeeding prevents diseases such as diarrhea and pneumonia which cause 40% of under-five deaths in Indonesia. The aim of this research is to find out what factors influence exclusive breastfeeding for working mothers. Analytical observational research method with quantitative methods. The population is all working mothers who have and breastfeed babies aged 0-6 months. The total sample was 63 respondents. The instrument used was a questionnaire. The results of statistical tests using chi square showed that the factors age, occupation and knowledge had ? values of 0.016, 0.001 and 0.024 < ? = 0.05, meaning there was a significant relationship, while the education and parity factors had ? values of 0.105 and 0.751 > ? = 0.05, then there is no relationship between education and parity and exclusive breastfeeding for working mothers. The conclusion is that the factors that influence exclusive breastfeeding for working mothers are age, occupation and knowledge.